Short-term Internet search using makes people rely on search engines when facing unknown issues - Wang, Yifan; Wu, Lingdan; Luo, Liang; Zhang, Yifen; Dong, Guangheng (PloS one, 2017)
The Internet search engines, which have powerful search/sort functions and ease of use features, have become an indispensable tool for many individuals. The current study is to test whether the short-term Internet search training can make people more dependent on it. Thirty-one subjects out of forty subjects completed the search training study which included a pre-test, a six-day's training of Internet search, and a post-test. During the pre- and post- tests, subjects were asked to search online the answers to 40 unusual questions, remember the answers and recall them in the scanner. Un-learned questions were randomly presented at the recalling stage in order to elicited search impulse. Comparing to the pre-test, subjects in the post-test reported higher impulse to use search engines to answer un-learned questions. Consistently, subjects showed higher brain activations in dorsolateral prefrontal cortex and anterior cingulate cortex in the post-test than in the pre-test. In addition, there were significant positive correlations self-reported search impulse and brain responses in the frontal areas. The results suggest that a simple six-day's Internet search training can make people dependent on the search tools when facing unknown issues. People are easily dependent on the Internet search engines.